First-principles study of carbon chemisorption on γ-Fe(111) surface - Hua,Y.W. (2010)
In order to study the interaction between γ-Fe and carbon, the geometry structures, surface relaxations, adsorption energies and electronic structures for carbon chemisorption at four different adsorption sites on γ-Fe(111) surface at a monolayer coverage of 1 were studied using density functional theory. The electronic structures were compared with the chemisorption of carbon on nickel (111) at the fcc hollow site. Based on the computational adsorption energies, the relative stabilities were described as follows: hcp hollow ≈ fcc hollow > top-on site, whereas the atomic carbon can not occupy the bridge sites stably. The partial density of states indicated the strong C(2p)-Fe(3d, 4s+p) and the wide C(2s+p)-Fe(3d) ionic bonds, which largely confined the electrons of the surface iron. Accordingly, the number of orbitals at the Fermi level for the iron in the surface is obviously less than that in the subsurface. Moreover, comparing the carbon chemisorptions on γ-Fe and nickel surface at the fcc hollow site, one could see that the number of orbitals at the Fermi level for carbon adsorbed on γ-Fe(111) is less than on Ni(111) surface. This could imply the weaker catalysis of γ-Fe than nickel for carbon atom.